2013
DOI: 10.1111/sdi.12073
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Transvenous Cardiac Devices on Vascular Access Patency in Hemodialysis Patients

Abstract: Creating a vascular access in the presence of a cardiovascular implantable electronic device (CIED) in a patient with or approaching end-stage renal disease can be challenging. In this study, we aimed to evaluate the impact of a CIED on the outcomes of vascular access creation in hemodialysis patients and determine their effects on vascular access patency. This is a single-center retrospective review of hemodialysis patients who underwent vascular access creation after CIED placement. Outcomes of vascular acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 24 publications
1
37
1
Order By: Relevance
“…In addition to upper extremity fistulas, these patients frequently require large bore nontunneled/tunneled central venous dialysis catheters during their lifetime . The risk of vascular access failure including central venous occlusion can be devastating …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to upper extremity fistulas, these patients frequently require large bore nontunneled/tunneled central venous dialysis catheters during their lifetime . The risk of vascular access failure including central venous occlusion can be devastating …”
Section: Discussionmentioning
confidence: 99%
“…2 The risk of vascular access failure including central venous occlusion can be devastating. 2,3 The incidence of cardiac rhythm disorder in the Chronic Kidney Disease (CKD) population remains high, frequently requiring a cardiac implantable electronic device. 4 A conventional cardiac implantable device with transvenous leads in such patients causes crowding of hardware in the central veins leading to a high incidence of central venous stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Stenosis results from the indwelling transvenous leads of IECD placed in the subclavian vein. 42 Treatment of central vein stenosis due to IECD with PTA alone has been evaluated by a multiple center study, which found the primary patency rates of 18% and 9% at 6 and 12 months, respectively 43 with need for more than 2.1 procedures per year to maintain long-term patency. 40 A retrospective review of 36 hemodialysis patients who underwent vascular access creation, the primary access failure for AVF created ipsilateral to an existing IECD was 78.9% versus 35.3% those created on the contralateral side.…”
Section: Question 7: How Do We Treat Central Venous Stenosis Secondarmentioning
confidence: 99%
“…40 A retrospective review of 36 hemodialysis patients who underwent vascular access creation, the primary access failure for AVF created ipsilateral to an existing IECD was 78.9% versus 35.3% those created on the contralateral side. 42 Treatment of central vein stenosis due to IECD with PTA alone has been evaluated by a multiple center study, which found the primary patency rates of 18% and 9% at 6 and 12 months, respectively 43 with need for more than 2.1 procedures per year to maintain long-term patency. The decision process with central vein stenosis in presence of ipsilateral IECD can be complex.…”
Section: Question 7: How Do We Treat Central Venous Stenosis Secondarmentioning
confidence: 99%
“…Patients aged greater than 65 years and with comorbidities are also increasing, especially those with diabetes and cardiovascular diseases. For these reasons, it is more common to see patients with cardiovascular implantable electronic devices (CIEDs) (1).…”
Section: Dear Editormentioning
confidence: 99%